Linguocultural Aspects of the Concept of "Qonaqjailylyq" (Hospitality) - Onalbayeva, Aigul; Zhumagulova, Bakitgul; Toktarova, Tolkyn; Aliyeva, Dinara; Kadyrov, Zhanbai; Yesmatova, Mendykyz (Forum for Linguistic Studies, 2024)
The aim of the studyis to identify the national and cultural features of the concept of "qonaqjailylyq" (hospitality) within the Kazakh linguistic worldview. To achieve this aim, methods of conceptual analysis, lexicographical research, and a free associative experiment involving 109 respondents were employed. The research is based on the analysis of lexicographical data, examples from literary texts, and the results of the associative experiment, which made it possible to reveal the key semantic and symbolic meanings of the studied concept. The findings indicate that hospitality in Kazakh culture encompasses material, emotional, and ritual elements, reflecting key national values such as respect, generosity, and warmth. The concept of "qonaqjailylyq" is closely linked to the traditions and cultural code of the Kazakh people and retains its significance in contemporary contexts. The study highlights the importance of hospitality as a component of intercultural communication and national identity, offering new approaches to its investigation.